Atlas eletrônico e socioeconômico sob a perspectiva da cartografia escolar no município de Restinga Sêca, RS - Cirolini, Angélica (2008)
In the education of Geography, the School Cartography is of basic importance, therefore the people, when she/he are alphabetized cartographyly, he/she has the capacity to interpret maps, images and other geographic representations. In this way, the didatic materials foreseen by the pedagogical conceptions are elaborated in analogical electronic digital means to subsidize the understanding of the local space. The Municipal Electronic Atlas come with a proposal innovative, therefore they motivate and invite learners and teachers to the practice of relating the space representations and also of providing the study of the lived space, sometimes building it, sometimes not building it through the observation of the socio-ambient elements, making with that the people wakes up bigger interest for the study of the geographic space. Inside this preamble, the present research has as main purpose to approach the importance of the study of the local space in the perspective of school cartography, in this case, Restinga Sêca county of RS through the elaboration of these atlases. The Atlas considered, in its conception, it possesses partial interaction with the user and it presents resources of multimedia with texts, images and animation. It allows to the student or user the manipulation of a set of maps, with the possibility to select the socio-economic subject or subjects that they desire to visualize, being able to combine predefined subjects and to configure a map. In this study, it structuralized itself of according to the municipal approach considering whole area of the county and, in specific the urban area, it chose twelve groups of socio-economics variables for the elaboration of the urban thematic maps, in both approaches was considered as space unit the census sector. Methodologily, it was followed the proposal of Brazilian Institute of Geography and Statistics for the definition of the variables according to Demographic Census 2000. In this way, a resource to verify if the map is fulfilling its function of communicator is the elaboration and application of tests with the users to verify the acceptability of it, in order to validate it as map pertaining to the Eletronic Atlas. The pilot test of these maps consist of many tests of isolated maps or of sets with the intention to become legitimate the maps that compose the Eletronic Socio-Economic of Restinga Sêca and to verify the learning easiness. The pilot test should be applied as a test to the public target: detainer and user of these Atlas. In this direction, it chose the five serie of high school due to be the period of training that the child starts the study of the cartography and studies of Restinga Sêca county. As results, it was observed that the rightness indices of peoples had been over of 60% practically at all the modules. In some cases, the index of rightnesss of people was low and the maps had been reworked and adapted for a better understanding. This facilitates the learning. Many maps had taken care of the goals and it was not necessary great alterations for their use. Ahead of the results, it considered the Atlas a didactic material and a resource of learning in digital means propitious digital for the use at school environment for the study of this county.